The authority of electronic evidence in criminal proof - Assistant Professor Dr. Qusay Ali Abbas (The college of law and political science journal, 2025)
This includes emails, text messages, social media posts, digital photographs, videos, and smartphones. Each type can provide crucial information about criminal activity or the intentions of individuals involved, legal framework the admissibility of electronic evidence in court depends on various factor, including authenticity, relevance, and reliability. legal standards, such as the rules of evidence in different jurisdictions, govern how this evidence can be presented and challenged, collection and preservation proper procedures must be followed when collecting electronic evidence to maintain its integrity, this often involves forensic analysis to ensure that the data is not altered or tampered with, chain of custody is critical to demonstrate that the evidence has been handled correctly, challenges the dynamic nature of digital data poses challenges, including issues related to encryption, data privacy, and jurisdiction, lnvestigators must navigate these complexities to effectively use electronic evidence in criminal cases.